2016
DOI: 10.1016/j.csda.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

High resolution simulation of nonstationary Gaussian random fields

Abstract: Simulation of random fields is a fundamental requirement for many spatial analyses. For small spatial networks, simulations can be produced using direct manipulations of the covariance matrix. Larger high resolution simulations are most easily available for stationary processes, where algorithms such as circulant embedding can be used to simulate a process at millions of locations. We discuss an approach to simulating high resolution nonstationary Gaussian processes that relies on generating a stationary rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Schlather (2012) and Kroese and Botev (2013) give recent overviews of fast algorithms to simulate stationary or isotropic random fields. The efficient generation of non-stationary Gaussian random fields at high spatial resolution is discussed by Kleiber (2016).…”
Section: Random Fieldsmentioning
confidence: 99%
“…Schlather (2012) and Kroese and Botev (2013) give recent overviews of fast algorithms to simulate stationary or isotropic random fields. The efficient generation of non-stationary Gaussian random fields at high spatial resolution is discussed by Kleiber (2016).…”
Section: Random Fieldsmentioning
confidence: 99%
“…Nychka et al (2015) introduced an idea based on Gaussian Markov random fields (GMRFs) and spatial autoregressive (SAR) models for nonstationary processes. Kleiber (2016) proposed an efficient nonstationary simulation method based on spatial deformation. However, it is computationally expensive to estimate the deformation function before performing the simulation.…”
Section: Implication For High-resolution Emulationmentioning
confidence: 99%
“…High-resolution nonstationary simulations are also challenging. Kleiber (2016) proposed combining the approaches of circular embedding and deformation to achieve an exact simulation. We propose a different approach using a sequentially conditional simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The residual process is a spatial Gaussian process. For weather derivatives markets application, its standard deviation is written as the product of a deterministic season and a GARCH process (Campbell and Diebold, 2011) while in case of the weather generators, full spatial models are used and the modelling effort mainly focuses on the covariance of the residual process (Kleiber, 2016). In the context of stochastic weather generators, it has been found that the introduction of regimes corresponding to typical weather patterns may help to better capture the non linearities of the meteorological variables (see (Ailliot et al, 2015a) and references therein).…”
Section: Daily Temperature Time Seriesmentioning
confidence: 99%